Novel method of simultaneous multiple immunogold localization on resin sections in high resolution scanning electron microscopy - Nebesarova, Jana; Wandrol, Petr; Vancova, Marie (Nanomedicine, 2016)
We present a new method of multiple immunolabeling that is suitable for a broad spectrum of biomedical applications. The general concept is to label both sides of the ultrathin section with the thickness of 70-80 nm with different antibodies conjugated to gold nanoparticles and to distinguish the labeled side by advanced imaging methods with high resolution scanning electron microscopy, such as by correlating images acquired at different energies of primary electrons using different signals. From the Clinical Editor: The use of transmission electron microscopy has become an indispensible tool in the detection of cellular proteins. In this short but interesting article, the authors described their new method of labeling and the identification of four different proteins simultaneously, which represents another advance in imaging technique.
Keywords: kovové nanočástice; zlato; Microscopy, Electrochemical, Scanning; Reproducibility of Results; Staining and Labeling; Immunohistochemistry; Sensitivity and Specificity; Acrylic Resins; Metal Nanoparticles; vylepšení obrazu; barvení a značení; senzitivita a specificita; akrylové pryskyřice; imunohistochemie; Image Enhancement; Microtomy; mikrotomie; reprodukovatelnost výsledků; Gold; skenovací elektrochemická mikroskopie